First record of Rosy Jewelfish Anthias noeli (Perciformes, Serranidae) in the littoral of Peru - Vera, Manuel (2023)
This work documents the first record of Anthias noeli Anderson & Baldwin, 2000 in Peru. Between 2016 and 2019, fifteen specimens were captured from the littoral of the Tumbes Department, located in the northernmost of Peru. Fresh photographs were taken of the specimens and meristic and morphometric analyses were conducted for species identification. Additionally, muscle tissue was extracted from five individuals to determine COI gene sequences. Phylogenetic analyses confirmed the specimens' identity as A. noeli, and the sequences were deposited in the public database BOLD Systems, representing the first deposited sequences for this species. This record expands the southern distribution of A. noeli.